Gender and American social science : the formative years - Silverberg, Helene, 1958- (Princeton University Press, 1998)
This collection of essays provides the first systematic and multidisciplinary analysis of the role of gender in the formation and dissemination of the American social sciences in the late nineteenth and early twentieth centuries. Other books have traced the history of academic social science without paying attention to gender, or have described women's social activism while ignoring its relation to the production of new social knowledge. In contrast, this volume draws long overdue attention to the ways in which changing gender relations shaped the development and organization of the new social knowledge.
Keywords: Social sciences -- United States -- History.; Women social scientists -- United States -- History.; Women -- United States -- History.; Sex role -- United States -- History.; Femmes spécialistes des sciences sociales -- États-Unis -- Histoire.; Femmes -- États-Unis -- Histoire.; Rôle selon le sexe -- États-Unis -- Histoire.; SOCIAL SCIENCE -- Women's Studies.; Sex role; Social sciences; Women; Women social scientists; United States; Begriff; Frauenforschung; Geschichte; Geschlecht; Geschlechterverhältnis; Geschlechterforschung; Sozialwissenschaften; Sozialwissenschaftlerin; Wissenschaftsentwicklung; USA; Aufsatzsammlung; Sekseverschillen.; Sociale wetenschappen.; Women social scientists -- United States.; Aufsatzsammlung.; History